Production of biosurfaction by locally isolated bacteria from petrochemical waste [microfilm] - 315259 Rusniza Mohd. Zawawi (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2005